Analysis System Payroll And Calculation Employee Salaries At Pt Lautan Jaya Semesta - Umdatul Aliyah; Angga Nugraha; Siti Sofiyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Politeknik Piksi Input Serang, 2023)
Purpose - This research was conducted at PT Lautan Jaya Semesta which aims to analyze the recitation system and calculation of employee gait at PT Lautan Jaya Semesta. Data collection techniques used are interviews and phaevas. Design/methodology/approach - The interview method is used to ask questions related to the calculation of employee salaries at PT Lautan Jaya. Semesta While the Observation Method is the data obtained about the payroll system. Finding - Based on the research results, the payroll system at PT Lautan Jaya Semesta can be said to be quite good because it involves important elements, including a network of procedures that make up the payroll system, related functions or sections in the payroll system, documents used . in the payroll system and interim control of the payroll system. consisting of organizations that have separate divisions, authorization systems and schat practices. While the calculation of the employee's net salary is obtained from the basic salary plus overtime pay, the meal allowance is reduced by deductions for PPH 21, BPJS. Originality-